Zen and the art of business communication : a step-by-step guide to improving your business writing skills - Luck, Susan L. (Corporate communication collection., 2016)
In today's online world, our professional image depends on our ability to communicate. Whether we're communicating by email, text, social media, written reports, or presentations, how we use our words often determines how others view us. This book offers tips and techniques that can improve anyone's professional image. It covers how to analyze your multiple audiences and strategies for communicating your message effectively for each; structuring your message for greatest readability and effect; persuasion and tone; and how to face your own fears of writing. The content is delivered in a simple, clear style that reflects the Zen approach of the title, perfect for both the entry-level employee and the seasoned executive.